Correlation governs the impurity (Ti, Zr, Hf) diffusion in face−centered cubic iridium through first−principles calculation. (June 2022) - Luo, Haiyu; Tang, Sai; Liang, Chaoping; Gong, Haoran
Abstract: Solid state diffusion depends on many factors, including crystal structure, vacancy concentration, energy barrier, jump frequency, correlation, etc. . In this work, those factors were systematically investigated for dilute IVB transition metals X (X = Ti, Zr, Hf) diffusion in face−centered cubic (FCC) Ir using first−principles calculations together with quasi−harmonic thermodynamics, climb−image nudged elastic band (CINEB), and five−frequency diffusion model. The results show that correlation which is often neglected in low melting point metals and alloys plays a key role in the impurity diffusion in Ir. The correlation factor which ranges from 10 −13  at 500 K to 10 −1  at 2000 K overturns the contributions from other factors, like vacancy concentration, energy barrier, and jump frequency. The diffusion coefficient of Ir−X (X = Ti, Zr, Hf) systems follows DHf  > DZr  > DTi, different from our traditional knowledge. Our findings not only give a good recount to the counterintuitive experimental phenomena in Ir oxidation resistance coating or ultrahigh−temperature Ir-based superalloys, but also provide valuable diffusion data for rational design of Ir-based materials for applications with harsh environment. Graphical abstract: Image 1 Highlights: Impurity (Ti, Zr, Hf) diffusion coefficient in Ir is exactly determined. Correlation factor successfully explains counterintuitive phenomena in Ir. Valuable diffusion data are given for the design of Ir-based materials.